2008
DOI: 10.1038/nm1775
|View full text |Cite
|
Sign up to set email alerts
|

Leptin controls adipose tissue lipogenesis via central, STAT3–independent mechanisms

Abstract: Leptin (encoded by Lep) controls body weight by regulating food intake and fuel partitioning. Obesity is characterized by leptin resistance and increased endocannabinoid tone. Here we show that leptin infused into the mediobasal hypothalamus (MBH) of rats inhibits white adipose tissue (WAT) lipogenesis, which occurs independently of signal transducer and activator of transcription-3 (STAT3) signaling. Correspondingly, transgenic inactivation of STAT3 signaling by mutation of the leptin receptor (s/s mice) lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
255
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(283 citation statements)
references
References 48 publications
19
255
0
9
Order By: Relevance
“…The extent to which the adipocyte mTOR pathway also becomes resistant to insulin or nutrient signals may be a critical determinant of the ability of the adipocyte to upregulate leptin production and close the feedback loop. In addition, hypothalamic leptin signaling through PI 3-kinase can activate sympathetic nerves to regulate adipocyte lipogenesis and endocannabinoid production in adipose tissue (11). This mechanism may also regulate leptin transcription and translation, providing direct central control of leptin production and an additional feedback loop.…”
Section: Future Directionsmentioning
confidence: 99%
“…The extent to which the adipocyte mTOR pathway also becomes resistant to insulin or nutrient signals may be a critical determinant of the ability of the adipocyte to upregulate leptin production and close the feedback loop. In addition, hypothalamic leptin signaling through PI 3-kinase can activate sympathetic nerves to regulate adipocyte lipogenesis and endocannabinoid production in adipose tissue (11). This mechanism may also regulate leptin transcription and translation, providing direct central control of leptin production and an additional feedback loop.…”
Section: Future Directionsmentioning
confidence: 99%
“…Many mechanisms have been proposed to explain the effect of leptin on peripheral glucose metabolism. Buettner et al proved that the cellular mechanisms underlying the hypothalamic regulation of hepatic glucose efflux depend on intact leptin STAT3 signaling [9]. A study by Morton et al indicates that hypothalamic leptin PI3K signaling is an important neuronal mechanism of glucose metabolism [10].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the sympathetic nervous system is involved in the transduction of leptin signals from the central nervous system to regulate peripheral glucose and lipid metabolism [9,48]. TH is a ratelimiting enzyme which synthesizes catecholamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the day of the clamp, conscious, unrestrained rats received the following MBH infusions at 0.33ul/h (CMA 400 syringe pump, CMA Microdialysis, Inc., North Chelmsford, MA): i) 0.9% Saline, ii) Glucose (Sigma-Aldrich, St. Louis, MO, 2mM for 6h; previously documented to lower glucose production (7)), iii) Glucose (2 mM) + leptin (R&D systems, Minneapolis, MN, 46 by guest on May 9, 2018 http://www.jbc.org/ Downloaded from ng/ul) (iv) lactate dehydrogenase blocker, oxamate (Millipore Sigma, Oakville, ON, Canada, 50 mM; first given as bolus (0.33ul)), (v) Glucose (2 mM) + oxamate (50 mM) or (vi) Glucose (2 mM) + leptin (46 ng/uL) + oxamate (50 mM). Leptin was infused at 33ng/h for 5h and this dose was chosen based on a previous study that reports leptin administered at 33 ng/h into the MBH for 6h exhibit metabolic control (31). In addition, we have chosen to infuse leptin 1h after glucose was started as we attempted to have the HFD rats first engage in glucose sensing mechanisms before examining whether leptin alters glucose sensing.…”
Section: Pancreatic (Basal Insulin)-euglycemic Clampsmentioning
confidence: 99%